The User Experience and Perception in Education of Digital Books in Librarians' Approaches to Library Services in Tangerang - Fitriani, Desi; Riady, Yasir; Evriza, Eka; Kuswanti, Eko; Sukatmi, Sri; Arisanty, Melisa; Karim, Muhammad Firman; Ajmal, Muhammad; rahim, Norizan Baba (CV Media Inti Teknologi, 2025)
Background of Study:Librarian attitudes significantly influence user satisfaction and engagement in library services. Positive interaction between librarians and users fosters a welcoming environment and enhances service effectiveness. Aims and Scope of Paper:This research aims to explore both the attitudes of librarians in providing services and users’ perceptions of those attitudes at the Tangerang Regency Library and Archives Office. Methods:A qualitative descriptive approach was employed. Data were collected through observation and interviews with three library users selected via purposive sampling. The data analysis followed three steps: data reduction, data presentation, and drawing conclusions. Result:Findings indicate that the average number of visitors to the Tangerang Regency Library and Archives Office from 2022 to 2023 was approximately 136,270. Users generally perceive librarians as friendly and kind. However, users often need to initiate interaction before receiving assistance, indicating a lack of proactive service. This shows that while the overall demeanor of librarians is positive, there remains a gap in attentiveness and sensitivity to user needs. Conclusion:Although librarians are perceived positively in terms of friendliness, service delivery can be improved by fostering a more proactive and responsive approach to user needs. These findings highlight the importance of continuous professional development for librarians to enhance user experience.